59. The Emergence of Open-Source Software in China - Pan, Guohua; Bonk, Curtis Jay (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2007)
The open-source software movement is gaining increasing momentum in China. Of the limited numbers of open-source software in China, Red Flag Linux stands out most strikingly, commanding 30 percent share of Chinese software market. Unlike the spontaneity of open-source movement in North America, open-source software development in China, such as Red Flag Linux, is an orchestrated activity wherein different levels of government play a vital role in sponsoring, incubating, and using open-source software, most conspicuously, Red Flag Linux. While there are no reports on open-source course management system in China, there are reports on the study and use of Western open-source course management systems for instruction and learning in Chinese higher education institutions. This paper discusses the current status of open-source software in China, including open-source course management software and associated tools and resources. Importantly, it describes the development model of Red Flag Linux, the most successful open-source software initiative in China. In addition, it explores the possibility of Chinese higher education institutions joining efforts to develop China’s own open-source course management system using the open-source development model established in North America. A timeline of major open-source projects of significance underway in China is provided. The paper concludes with a discussion of the potential for applying the open-source software development model to open and distance education in China.